Is there rationale for the cuff pressures prescribed for blood flow restriction exercise? A systematic review - Clarkson, M. J.; May, A. K.; Warmington, S. A. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Background: Blood flow restriction exercise has increasingly broad applications among healthy and clinical populations. Ensuring the technique is applied in a safe, controlled, and beneficial way for target populations is essential. Individualized cuff pressures are a favored method for achieving this. However, there remains marked inconsistency in how individualized cuff pressures are applied. Objectives: To quantify the cuff pressures used in the broader blood flow restriction exercise literature, and determine whether there is clear justification for the choice of pressure prescribed. Methods: Studies were included in this review from database searches if they employed an experimental design using original data, involved either acute or chronic exercise using blood flow restriction, and they assessed limb or arterial occlusion pressure to determine an individualized cuff pressure. Methodologies of the studies were evaluated using a bespoke quality assessment tool. Results: Fifty-one studies met the inclusion criteria. Individualized cuff pressures ranged from 30% to 100% arterial occlusion pressure. Only 7 out of 52 studies attempted to justify the individualized cuff pressure applied during exercise. The mean quality rating for all studies was 11.1 ± 1.2 out of 13. Conclusions: The broader blood flow restriction exercise literature uses markedly heterogeneous prescription variables despite using individualized cuff pressures. This is problematic in the absence of any clear justification for the individualized cuff pressures selected. Systematically measuring and reporting all relevant acute responses and training adaptations to the full spectrum of BFR pressures alongside increased clarity around the methodology used during blood flow restriction exercise is paramount.